The Facilitation of Pericardiocentesis Using Imaging Techniques. A Case Report - Manițiu Ioan; Cobârje Iulia; Bitea Ionuț; Cojan Radu; Bebeşelea Andra-Maria (Journal of Cardiovascular Emergencies, 2016)
Introduction: Pericardiocentesis is a procedure performed for diagnostic and therapeutic purposes, and it consists in draining the pericardial effusion liquid in sterile conditions. The accumulation of fluid in the pericardial space may be caused by several systemic conditions, including viral or bacterial infections, autoimmune disease, cancer, as well as thyroid malfunction. A rapidly growing pericardial effusion can lead to cardiac tamponade, and consequently to acute hypodiastolic heart failure.